2016
DOI: 10.1097/md.0000000000004405
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists working in clinics have increased risk for new-onset spine disorders

Abstract: Health care professionals are known to have a high risk for work-related musculoskeletal disorders. However, the information on the risk of new-onset spine-related musculoskeletal disorders (SRMDs) in health care professionals is insufficient. This study aimed to investigate new-onset spine disorder associations among physical, occupational, and pharmacy health care professionals working in different workplaces.Taiwan's National Health Insurance Research Database for registered medical personnel claims from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
1
10
0
1
Order By: Relevance
“…[ 20 ] Furthermore, the symptoms of LBP were found to have the greatest occurrence (53.10% vs 55.50%), indicating that LBP is the most frequently seen MSD. [ 20 ] Another study revealed that the mean time from obtaining a registered license to developing a SRMD is 1.41 to 5.57 years, [ 21 ] which is similar to our result of 4.25 years.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…[ 20 ] Furthermore, the symptoms of LBP were found to have the greatest occurrence (53.10% vs 55.50%), indicating that LBP is the most frequently seen MSD. [ 20 ] Another study revealed that the mean time from obtaining a registered license to developing a SRMD is 1.41 to 5.57 years, [ 21 ] which is similar to our result of 4.25 years.…”
Section: Discussionsupporting
confidence: 87%
“…A 12-year population-based study of medical staff revealed that the incidence of spine-related MSDs (SRMDs; a symptom of LBP) of hospital pharmacists is 19.60%, which is between those for PTs (32.12%) and OTs (16.97%). [ 21 ] However, that study enrolled medical staff aged between 18 and 65 years, which covered a wider age range than our study, therefore its incidences were expected to be higher than the results of our study. Besides, higher incidences of LBP and/or SRMDs were also found in populations aged above 40 years in previously published studies.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Another recent study by Epstein et al [ 12 ] has affirmed that the risk of developing MSDs increases due to force of movement, monotonous tasks, lack of control over job, and poor communication skills. Besides, work conditions like pace of work, weight of handling object, and layout of working station also significantly influence the development of MSDs [ 13 ]. The development of musculoskeletal pain was discussed by Lietz et al [ 14 ] and the analysis showed that the risk of MSDs increases on account of the use of vibrating equipment, adoption of consistent static posture, and utilization of psychomotor skills.…”
Section: Introductionmentioning
confidence: 99%
“…Kas-iskelet sistemi rahatsızlıkları, kas, tendon, bağ, eklem, periferik sinir ve kan damarlarını etkileyen çok çeşitli enflamatuar ve dejeneratif durumları içerir 1 . Kas-iskelet sistemi rahatsızlıkları bireylerin sosyal ve ekonomik sorunlar yaşamalarına neden olmasının 2 yanında yaşam kalitesini de olumsuz yönde etkilemektedir 3,4 . Bunun yanı sıra, kas-iskelet sistemi rahatsızlıkları %45'e varan yüksek görülme sıklığı ile de dikkat çekmektedir 5,6 .…”
Section: Introductionunclassified